Urban Soils Principles and Practice - Rate, Andrew W. (Cham : Springer International Publishing : Imprint: Springer, 2022)
Urbanisation of the world's population is an increasing trend; in China, for example, the proportion of the population living in cities increased from 13% in 1950 to 45% in 2010 (World Bank data). Australia is one of the world's top ten urbanised countries with population greater than ten million, with approximately 90% of its population living in cities, mainly along Australia's coast. The most rapidly urbanising populations are currently in nations of the African continent. Soils in urban areas have multiple functions which are becoming more valued by urban communities: soils supply water, nutrients and physical support for urban plant and animal communities (parks, reserves, gardens), and are becoming increasingly valued for growing food. Soils may be used for building foundations, or as building materials themselves. Urban hydrology relies on the existence of unsealed soils for aquifer protection and flood control. This book is designed primarily as an educational text, but it also reflects current developments in research, and provides readers with an authoritative gateway to the primary literature. It presents the importance of urban ecosystems and the impacts of global change. It examines pedogenesis of urban soils: natural materials affected by urban phenomena, and natural processes acting on urban materials, including an examination of different climatic zones. There is a focus on soils formed on landfill, reclaimed land, dredge spoils as well as soil-related changes in urban geomorphology. There is plenty of discussion on urban soil as a source and sink as well as soil geochemistry and health. .
1. Urban Ecosystems: Soils and the Rise and Fall of Cities -- 2. Formation and Properties of Urban Soils -- 3. Spatial Variability and Data Analysis in Urban Soils -- 4. Urban Soil Functions -- 5. Urban Soil Physics -- 6. Inorganic Contaminants in Urban Soils -- 7. Organic Contaminants in Urban Soils -- 8. Soil Biological Processes in Urban Soils -- 9. Urban Soil as a Source and Sink -- 10. Urban Soil and Human Health -- 11. Urban Soil Remediation -- 12. The Future of Urban Soils.
Keywords: Soil science; Physical geography; Urban ecology (Biology).; Human ecology-Study and teaching; Geochemistry; Soil Science; Earth System Sciences; Urban Ecology; Earth System Sciences; Environmental Studies; Geochemistry